Developing rapport in inter-professional communication: Insights for international medical graduates. (April 2016) - Yates, Lynda; Dahm, Maria R.; Roger, Peter; Cartmill, John
Abstract: Many Western countries including Australia have become reliant on international medical graduates (IMGs) to strengthen their medical workforce. In Australia, the majority of IMGs are now from non-English speaking backgrounds and work in medical and communicative environments in which they were not raised or trained themselves. They therefore face the challenge of understanding unfamiliar hospital systems and guidelines, and a new set of cultural and communicative parameters. In this paper, we report findings from a pilot study investigating the communicative challenges that IMGs face in simulated medical handovers in an Australian hospital context. Using a case study approach and tools from applied linguistics and intercultural pragmatics, we analyse the discourse of two doctors to identify some of the discourse features that native English-speaking and expert medical practitioners use to establish and maintain rapport with colleagues. We draw on the distinction between the pragmalinguistic and sociopragmatic aspects of the inter-professional context to illuminate the different areas of communication that might be tackled explicitly and systematically as part of IMG preparation for practice in Australia. In this way we illustrate how discourse data can contribute to an evidence base from which principled approaches to communication training for IMGs may be developed. Highlights: International and local doctors were observed during handovers with a nurse. We identified discourse features expressing rapport in inter-professional contexts. Cultural expectations and linguistic realisations of teamwork can trouble IMGs. ESP courses should include sociopragmatic and pragmalinguistic aspects of rapport.